Access is not enough! Reconceptualizing Data Quality as a Public Value in Times of Platformization and European Regulation - Peters, Yannik; Weller, Katrin (AoIR Selected Papers of Internet Research, 2026)
Questions regarding quality digital platform data have gained significant attention and research focus in recent years as new error frameworks and data quality dimensions have been developed. With this contribution we link recent work from the area of data quality research with critical reflections on platformization and argue that the quality of online platform data cannot solely be understood as a methodological, internal research construct, but also as a contested concept in which various actors from politics, the tech industry and academia negotiate and represent specific interests. On the one hand, digital platforms increased the commoditization of data quality, e.g. though monetized APIs. On the other hand, this strategy of digital platforms has now increasingly become the subject of political efforts of regulation, especially in the European Union (EU). The Digital Services Act (DSA) includes provisions for access to platform data by researchers. We problematize that the current debate and the DSA are particularly about data access from platforms, but not data quality in general. The consequence of this is that even if platforms grant access to data, the actual purpose of conducting reliable and socially relevant research is undermined by a lack of data quality. As a potential solution, we identify the need for new actors to assess the quality of platform data and provide long term accountability and supportive infrastructure for quality assessments.